From Apostolicity to Catholicity: John Henry Newman's Ecumenical Ecclesiology in Light of Vatican II. - Blanco-Sarto, Pablo (Journal of Ecumenical Studies)
Newman started from an evangelical individualism but later discovered the Catholic Church's sacramentality and apostolicity. His ecclesiological sight had an organic evolution, starting from the ecclesiology of the Fathers. In his Anglican period, he tried to defend the apostolic character of the Church of England, so there is an ecclesiological development from the via media and the "branch theory" to the doctrine of the elementa Ecclesiae (UR, nos. 5–6). He also spoke about the invisible church, as in LG, no. 1. The reform, purification, and sanctity of the church is another important issue: Ecclesia semper purificanda (cf. LG, no. 8). In this sense, Newman was a prophet of Vatican II's ecumenical ecclesiology. This evolution in his writings is analyzed in this study from an Anglican-Roman Catholic perspective.